Aspirin Use and Mortality in Two Contemporary US Cohorts. Issue 1 (January 2018) - Huang, Wen-Yi; Daugherty, Sarah E.; Shiels, Meredith S.; Purdue, Mark P.; Freedman, Neal D.; Abnet, Christian C.; Hollenbeck, Albert R.; Hayes, Richard B.; Silverman, Debra T.; Berndt, Sonja I.
Abstract : Background: Daily aspirin use has been recommended for secondary prevention of cardiovascular disease, but its use for primary prevention remains controversial. Methods: We followed 440, 277 men and women from the NIH-AARP Diet and Health Study (ages 50–71) and the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial (ages 55–74) for mortality for 13 years on average. Frequency of aspirin use was ascertained through self-report, and cause of death by death certificates. We calculated multivariate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality using Cox proportional hazards models for each cohort and combined by meta-analysis. Results: We found a consistent U-shaped relationship between aspirin use and mortality in both studies, with differential risk patterns for cardiovascular mortality by disease history. Among individuals with a history of cardiovascular disease, daily aspirin use was associated with reduced cardiovascular mortality [HR = 0.78 (95% CI, 0.74, 0.82)]. However, among those without a previous history, we observed no protection for daily aspirin users [HR = 1.06 (1.02, 1.11)], and elevated risk of cardiovascular mortality for those taking aspirin twice daily or more [HR = 1.29 (1.19, 1.39)]. Elevated risk persisted even among participants who lived beyond 5 years of follow-up and used aspirin without other nonsteroidal antiinflammatory drugs [HR = 1.31 (1.17, 1.47)]. Conclusions: Results from these 2 large population-based US cohorts confirm the utility of daily aspirin use for secondary prevention of cardiovascular mortality; however, our data suggest that caution should be exercised in more frequent use, particularly among individuals without a history of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.